Gender, agriculture and sustainable livelihood among rural farmers in northern Ghana - Azumah, Francess Dufie; Onzaberigu, Nachinaab John; Adongo, Awinaba Amoah (Economic change and restructuring, 2023)
Women play an important role in agriculture and rural economic development. Gender access to farmland and its impact on agricultural productivity, as well as gender-based sustainable livelihoods, are all part of rural development policy. Understanding or gaining insight into gender access to agricultural land and long-term sustainability aids in improving the needs of rural women in land acquisition. The purpose of this study was to investigate gender access to farmland and its impact on agricultural productivity and gender sustainable livelihood, as well as the constraints and methods involved in farmland access and acquisition. A quantitative approach was used in the study. Data were collected through questionnaire from 120 rural farmers from four communities using a simple random sampling method. The findings revealed that insufficient fertile farmland is a major factor influencing agricultural productivity. In the study areas, patriarchal inheritance emerged as the primary mode of farmland access and acquisition, but it also acted as a constraint to gender farmland access. Due to patriarchy, male farmers were said to have easier access to farmland than their female partners. The study also concluded that women are marginalized when it comes to acquiring land for agricultural production, which has an impact on the gender's long-term livelihood sustainability. To address the challenges confronting rural gender farmland access, a policy to ensure gender equality in farmland access is required.